Palynological Studies and Lectotypification of Malpighiaceae in Thailand - Chaisongkram, Wanwipha; Tubtamat, Maneenuch; Kulpholmuang, Wilaiwan; Chantaranothai, Pranom (Tropical Natural History, 2022)
The pollen morphology of 19 species belonging to six genera of the Malpighiaceae in Thailand was examined by both light- and scanning electron microscopy. Pollen grains were found to be monad and bilateral or radial symmetry. They were apolar, isopolar or heteropolar with a high range of size from very small to medium. The shapes were oblate, oblate spheroidal, prolate spheroidal and subprolate. The ambs were triangular, quadrangular, quinquangular and subcircular. Aperture types were 3−4-colporate, 3-colporate with parasyncolporate, 4-porate, polyporate, monosulcate and trichotomosulcate. Five pollen types were proposed based on the exine sculpturing viz. fossulate, granulate, perforate, rugulate and verrucate types. Lectotypes for nine taxa of Malpighiaceae were herein designated, namely Aspidopterys thorelii, Brachylophon anastomosans, Hiptage bullata, H. candicans, H. candicans var. angustifolia, H. condita, H. detergens, H. glabrifolia and H. lucida.